Effects of antioxidant enzyme polymorphisms on ozone-induced lung function changes - Chen, C. (2007)
Chronic exposure to ozone (O(3)) can cause changes in lung function that may reflect remodelling of small airways. It is likely that antioxidant enzyme function affects susceptibility to O(3). The aim of the present study was to determine whether polymorphisms in antioxidant enzyme (GSTM1, GSTP1 and NQO1) genes affect the risk of lung function changes related to chronic exposure to O(3). In total, 210 young adults who participated in a previous study, which showed a relationship between lifetime exposure to O(3) and decreased lung function, were genotyped. Multivariable linear regression was used to model sex-specific associations between genotypes and O(3)-related lung function changes, adjusting for height, weight, lifetime exposure to nitrogen dioxide and particles with a 50% cut-off aerodynamic diameter of 10 μm, and self-identified race/ethnicity. The GSTM1-null/NQO1 Pro187Pro-combination genotype was significantly associated with increased risk of an O(3)-related decrease in mean forced expiratory flow between 25–75% of forced vital capacity in females (parameter estimate ± SE −75 ± 35 mL·s(−1)), while the GSTP1 Val105 variant genotypes were significantly associated with greater risk of an O(3)-related decrease in mean forced expiratory flow at 75% of forced vital capacity in males (−81 ± 31 mL·s(−1)). GSTM1-null status was not significantly associated with any O(3)-related changes in lung function in either sex. The current authors conclude that the effects of antioxidant enzyme gene polymorphisms on the risk of decreased lung function related to chronic exposure to ozone may be modified by sex-specific factors.